IFN-β production induced by PRRSV is affected by GP3 quantity control and CLND4 interaction - Dexin Li; Xinyu Cui; Yingchao Li; Qin Zhang; Hongyan Gao; Youbo Li; Yanmeng Hou; Hongjie Yuan; Yihong Xiao (Veterinary Research)
Abstract Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most harmful pathogens in the swine industry. Our previous studies demonstrated that the small extracellular domain (ECL2) of CLDN4 effectively blocks PRRSV infection. In this study, we explored the in vivo administration of swine ECL2 (sECL2) and found that it blocked HP-PRRSV infection and alleviated histopathological changes in organs. Notably, sECL2 stimulated cytokine production in the lungs. We observed that CLDN4 upregulated the expression of IFN-β at low doses of GP3. While high doses of GP3 inhibited the activity of the IFN-β promotor, regardless of whether CLDN4 was present. GP3 also downregulated IFN-β by decreasing the phosphorylation of TBK1 and IRF3. These findings highlight functional differences in GP3 under quantity control, which account for the variations in IFN-β induction during the early and late stages of infection. Our results indicate that sECL2 is a promising candidate drug for developing treatments to control PRRS.